Tap water versus sterile saline solution in the colonisation of skin wounds. Issue 4 (8th June 2015) - Resende, Margarida MC; Rocha, Cleber A; Corrêa, Nely FM; Veiga, Renato RG; Passos, Sandro JF; Novo, Neil F; Juliano, Yara; Damasceno, Carlos AV
Abstract: Irrigating wounds with tap water does not increase colonisation, but controlled studies are required for further evidence. Microbial colonisation was assessed in skin wounds, before and after irrigation with tap water, and was compared with irrigation using 0·9% sodium chloride sterile solution. The study included 120 subjects with chronic, traumatic, vascular, pressure or neuropathic wounds. A total of 60 wounds were randomly assigned to be irrigated with tap water (tap water group) and another 60 to be irrigated with 0·9% sodium chloride sterile solution (saline group), at a pressure of 0·46–0·54 PSI. Samples were collected from the centre of each wound using Levine's technique, before and after irrigation, and cultivated in thioglycollate, hypertonic mannitol agar, eosin methylene blue (EMB) agar, blood agar and Sabouraud agar at 37°C for 72 hours. There was concordance (kappa test) and discordance (McNemar test) regarding the count of positive and/or negative samples before and after irrigation in each group. The proportion of reduction of positive samples was similar for both groups in all cultures. Colony‐forming unit count before and after irrigation was similar in both groups and in all cultures, except for the culture in hypertonic mannitol agar from the tap water group, for which the count was lower after irrigation (Wilcoxon z = 2·05, P = 0·041). It is concluded that skin wound irrigation with tap water leads to further reduction of Gram‐positive bacteria compared with 0·9% sodium chloride sterile solution, with no difference in colonisation of haemolytic bacteria, Gram‐negative bacteria and fungi.